Microscopic agglutination test results. - Paul Le Turnier (7829654) (2025)
Background Leptospirosis is a zoonotic disease of increasing importance in French Guiana. It particularly affects subjects living in precarious conditions. We aimed to determine the seroprevalence and the risk of exposure to leptospirosis among inhabitants of three informal settlements in French Guiana. Methods A serological investigation was conducted in 2022 in three informal settlements in the area of Cayenne, the main city of French Guiana. Leptospirosis exposure factors were assessed in volunteers aged > 15 through a standardized questionnaire. Leptospirosis seroprevalence was evaluated with Microscopic Agglutination Test (MAT) using 17 pathogenic Leptospira antigens with a reactivity threshold of 1:100. Results In 266 participants, median [IQR] age was 42 [34–52] and male to female sex ratio was 0.9. Most participants were migrants (96%), mainly from Haiti (83%), and lived in the study area for at least 2 years (82%). Household rodent exposure (89%) and use of other water sources than collective standpoint (92%) were common. An at-risk occupation was reported for 68% of working participants. Leptospirosis seroprevalence was 7.5% (95% CI [4.7-11.4]) with Ballum and Icterohaemorrhagiae as the main serogroups. Foot skin exposure in wet environments was associated with reactive serum (OR 7.6, 95% CI [1.1 - 326.7]). Conclusion Despite a high theoretical risk of leptospirosis exposure among informal settlements inhabitants, only a few participants were seroreactive for Leptospira. This may suggest that despite at-risk exposures the effective transmission of leptospirosis remains limited within the study area. Broader serological surveys and environmental studies should clarify the areas of at-risk leptospirosis transmission in French Guiana.